Pneumomediastinum Mimicking Congenital Pulmonary Airway Malformation - Ranjit I Kylat (MDPI AG, 2019)
Pneumomediastinum is the collection of free air in the mediastinum. Its incidence is higher in preterm infants and those on positive airway pressure support or on mechanical ventilation. But it has decreased dramatically after the introduction of surfactant and synchronized, non-invasive mechanical ventilation. Underlying cystic lesions could also increase the risk of pneumomediastinum and other air leak syndromes. Most cases resolve spontaneously but rare hemodynamic compromise may require ultrasound-guided intervention.